A theoretical study of the modal dispersion characteristics of an annular circular waveguide with helical winding as the outer cladding - Srivastava S.K.; Ojha S.P. (My University, 2025)
In this present communication, we introduce a new type of annular optical waveguide whose outer cladding is made of sheath helix. The sheath helix is made up of the dielectric material of lower refractive index than the core materials. Using vector approach, the general characteristic equation for the proposed waveguide has been derived. The modal dispersion characteristics for the lowest-order modes for different pitch angles are determined and analyzed. We observe that there is no effect of pitch angles on dispersion curve nearly up to 89° but drastic change is observed at 90° and above pitch angle. On comparison of helically inner cladded annular circular waveguide, we have found that there is not the existence of the negative dispersion curve and photonic band gap in the helically outer cladded annular circular waveguide. It means only the inner cladding is responsible for the negative dispersion as well as photonic band gap. There is no effect of the outer cladding. © 2006 Elsevier GmbH. All rights reserved.